Publisher Correction: Super-resolution fight club: assessment of 2D and 3D single-molecule localization microscopy software - Sage, Daniel; Pham, Thanh-An; Babcock, Hazen; Lukes, Tomas; Pengo, Thomas; Chao, Jerry; Velmurugan, Ramraj; Herbert, Alex; Agrawal, Anurag; Colabrese, Silvia; Wheeler, Ann; Archetti, Anna; et al. (Nature methods, 2019)
In the version of this paper originally published, Figure 4a contained errors that were introduced during typesetting. The bottom 11° ThunderSTORM image is an xz view but was incorrectly labeled as xy, and the low x-axis value in the four line profiles was incorrectly set as -60 instead of -50. These errors have been corrected in the PDF and HTML versions of the paper.